The Influence of The Work Environment on Job Satisfaction of Samsat Office UPT Revenue Regional Region of Makassar 1 - Darmayanti, Puput Amelia; Nurman; Dipoatmodjo, Tenri S.P.; Tawe, Amiruddin; Haeruddin, Muh. Ikhwan Maulana (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of the work environment on the job satisfaction of the Samsat Office UPT Regional Income Makassar 1 regionally partially and simultaneously. The samples used were 40 employees of the UPT Regional Revenue Samsat Office Makassar Region 1. The data collection technique was carried out by means of a questionnaire. Data analysis techniques consist of validity test, reliability test, classic assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test, multiple linear analysis test, hypothesis test, test of the coefficient of determination. Physical Work Environment Variables have a positive and significant effect on job satisfaction, and Non-Physical Work Environment variables have a positive and significant effect on job satisfaction. The most dominant variable affecting job satisfaction is the non-physical work environment variable. The dependent variable job satisfaction can be explained by variables consisting of the physical work environment, and the remaining non-physical work environment is explained by other variables that were not examined in this study.